The Road Performance Analysis in Jalan Ahmad Yani Batam Using IHCM 1997 - Wincent Wincent; Andri Irfan Rifai; Muhammad Isradi (International Journal Labs, 2022)
One of the congestion points that will be analyzed is on Jalan Ahmad Yani, Batam. Congestion will occur during the hours of entering and returning from work. Congestion occurs due to high levels of vehicles that exceed the capacity of the road. Road widening also had a temporary negative impact as traffic congestion worsened. The purpose of this paper is to analyze road performance on Jalan Ahmad Yani (Kepri Mall – Batamindo industrial area). All data is processed to obtain the road service level using the IHCM 1997 guidelines. From direct surveys and data calculations obtained, total traffic flow during peak hour is 5490 pcu/hour, free flow speed (FV) of light vehicles (LV) is 54.72 km/hour and 57 km/hour for each lane. The total capacity is 10407.21 pcu/hour, the degree of saturation per lane is 0.52 and 0.54, and the level of service of Jalan Ahmad Yani value is C.